ANALISIS DAMPAK LINGKUNGAN AKIBAT PENGGUNAAN KEMASAN PLASTIK DALAM KEGIATAN EKONOMI - Evan Hamdani; Harahap, Muhammad Ikhsan; Imsar Imsar (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The use of plastic packaging in economic activities is increasing along with the rapid development of trade, especially through e-commerce, but this raises serious environmental problems. The main problem of this research is What are the environmental impacts caused by the use of plastic packaging. This study aims to analyze the environmental impacts of the use of plastic packaging using a literature review method. The results of the study indicate that plastic packaging contributes to land, water, and marine pollution, causes an increase in the volume of single-use waste, and has the potential to harm health through the accumulation of microplastics. The conclusion of the study emphasizes the need for real efforts from the government, business actors, and the community to reduce the use of plastic while promoting environmentally friendly packaging alternatives in order to support sustainable development.